Comparison Study Of Bacteria On Pangasius djambal In Ponds And River In Pagelaran Lampung - Nurhaida Widiani; Nita Ayu Agustin; Marlina Kamelia; Dwijowati Asih Saputri (Biota, 2020)
Pangasius djambal is one of the popular fish. The obstacle in this fish culture is the presence of bacterial attack, which is thought to originate from the waters where the fish live. This study aims to determine the differences in the number of bacteria found in the body of P djambal that are cultivated in ponds and those that live in rivers. Based on research, it is known that the number of bacteria found in the body of fish originating from rivers is more than the number of bacteria originating from ponds. The results showed the number of bacteria in the gills of fish from river reached 250 x 107 Cfu/g and in mucus 199 x 107 Cfu/g. While the number of fish bacteria originating from ponds in the gills section is 204 x 107 Cfu/g and in the mucus section is 131x107 Cfu/g.